Navigating the Minefield: Managing Refusal of Medical Care in Older Adults with Chronic Symptoms of Mental Illness - O'Cionnaith C (Dove Medical Press, 2021)
Cathal O’Cionnaith,1 Anne PF Wand,1– 3 Carmelle Peisah3,4 1Older Persons Mental Health Service, Jara Unit, Concord Centre for Mental Health, Concord Repatriation General Hospital, Concord, NSW, Australia; 2Specialty of Psychiatry, Faculty of Medicine and Health, University of Sydney, Sydney, NSW, Australia; 3Discipline of Psychiatry, Faculty of Medicine, University of New South Wales, Sydney, NSW, Australia; 4Capacity Australia, Crows Nest, NSW, AustraliaCorrespondence: Anne PF WandOlder Persons Mental Health Service, Jara Unit, Concord Centre for Mental Health, Concord Repatriation General Hospital, 109 Hospital Road, Concord, NSW, 2139, AustraliaTel +61297678940Fax +61297678944Email a.wand@unsw.edu.auPurpose: The purpose of this case series is to illustrate the complexity of considerations across health (physical and mental), ethical, human rights and practical domains when an older adult with chronic symptoms of mental illness refuses treatment for a serious medical comorbidity. A broad understanding of these considerations may assist health care professionals in navigating this challenging but common aspect of clinical practice.Case Presentation: Three detailed case reports are described. Participants were older adults with an acute presentation of a chronic mental illness, admitted to a specialized older persons mental health inpatient unit (OPMHU) in an Australian metropolitan hospital. Significant comorbid medical issues were detected or arose during the admission and the patient refused the recommended medical intervention. Data extracted from patients’ medical records were analyzed and synthesized into detailed case reports using descriptive techniques. Each patient was assessed as lacking capacity for healthcare and treatment consent and did not have relatives or friends to assist with supported decision-making. Multifaceted aspects of decision-making and management are highlighted.Conclusion: There are multiple complex issues to consider when an older adult with chronic symptoms of mental illness refuses treatment for serious comorbid medical conditions. In addition to optimizing management of the underlying mental illness (which may be impairing capacity to make healthcare decisions), clinicians should adopt a role of advocacy for their patients in considering the potential impact of ageism and stigma on management plans and inequities in physical healthcare. Consultation with specialist medical teams should incorporate multifaceted considerations such as potentially inappropriate treatment and optimum setting of care. Equally important is reflective practice; considering whether treatment decisions may infringe upon human rights or cause trauma.Keywords: treatment refusal, human rights, capacity, ageism, psychiatric